2016
DOI: 10.1182/blood.v128.22.1207.1207
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Residual Disease Monitoring in Acute Myeloid Leukemia (AML) with Translocation t(8;21)(q22;q22): Results of the AML Study Group (AMLSG)

Abstract: Background: Acute myeloid leukemia (AML) with t(8;21)(q22;q22) results in the formation of the RUNX1-RUNX1T1 fusion transcript which can be used to monitor minimal residual disease (MRD) by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR). Early identification of patients (pts) with a high risk of relapse will allow pre-emptive therapy including allogeneic hematopoietic cell transplantation (alloHCT). Recent studies in AML with NPM1 mutation or the CBFB-MYH11 gene fusion revealed that MRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Normalized to 10 5 ABL1 copies, after only one cycle of intensive chemotherapy, MRD copy numbers of <100 in BM or <10 in PB for CBFB-MYH11 AML [16] and <500 in BM or <1000 in PB, as well as a >3 log [16] or >2.5 log [48] BM MRD reduction from diagnosis for RUNX1-RUNX1T1 AML have been shown to associate with lower relapse risk and longer OS. However, there are also studies not finding a prognostic significance at this early time-point [11,49,50]. After two cycles of chemotherapy, either absolute MRD of <0.1% (normalized to ABL1 ) [50] or a >3 log MRD reduction from diagnosis [48,49,51] associated with a lower relapse risk in both CBF-AML subtypes while MRD-negativity was no prognostic factor in RUNX1 - RUNX1T1 AML at this time-point [11].…”
Section: Methods For Mrd Detectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Normalized to 10 5 ABL1 copies, after only one cycle of intensive chemotherapy, MRD copy numbers of <100 in BM or <10 in PB for CBFB-MYH11 AML [16] and <500 in BM or <1000 in PB, as well as a >3 log [16] or >2.5 log [48] BM MRD reduction from diagnosis for RUNX1-RUNX1T1 AML have been shown to associate with lower relapse risk and longer OS. However, there are also studies not finding a prognostic significance at this early time-point [11,49,50]. After two cycles of chemotherapy, either absolute MRD of <0.1% (normalized to ABL1 ) [50] or a >3 log MRD reduction from diagnosis [48,49,51] associated with a lower relapse risk in both CBF-AML subtypes while MRD-negativity was no prognostic factor in RUNX1 - RUNX1T1 AML at this time-point [11].…”
Section: Methods For Mrd Detectionmentioning
confidence: 99%
“…However, there are also studies not finding a prognostic significance at this early time-point [11,49,50]. After two cycles of chemotherapy, either absolute MRD of <0.1% (normalized to ABL1 ) [50] or a >3 log MRD reduction from diagnosis [48,49,51] associated with a lower relapse risk in both CBF-AML subtypes while MRD-negativity was no prognostic factor in RUNX1 - RUNX1T1 AML at this time-point [11]. Normalized to 10 5 ABL1 copies, after three cycles of chemotherapy, MRD copy numbers of <10 in PB for CBFB-MYH11 [16] and <500 in BM, as well as a >4 log BM MRD reduction for RUNX1-RUNX1T1 AML [16] were prognostic.…”
Section: Methods For Mrd Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…MRD denotes the presence of leukemia cells at frequencies below that of routine measurement by morphology or cytogenetics, with sensitivity down to 1 in 10 4 to 1 in 10 6 of total leukocytes, as compared to 1 in 20 in standard morphology [ 5 ]. Numerous studies have shown the power of MRD in AML in predicting risk of relapse and overall survival [ 6 , 7 , 8 , 9 ]. In the setting of allogeneic stem cell transplant (alloSCT), those who proceed to transplant with MRD positivity have been shown to have a risk of relapse and 3-year overall survival similar to those with active AML [ 10 ].…”
Section: Introductionmentioning
confidence: 99%